Effectiveness of prostaglandin E1 in patients with mixed arterial and venous ulcers of the lower limbs. Issue 5 (5th August 2014) - De Caridi, Giovanni; Massara, Mafalda; Stilo, Francesco; Spinelli, Francesco; Grande, Raffaele; Butrico, Lucia; de Franciscis, Stefano; Serra, Raffaele
Abstract: Mixed arterial and venous ulcers of the lower limbs are present in around 15–30% of patients with chronic venous ulcers (CVUs) and are considered difficult‐to‐heal wounds. The aim of this study was to evaluate the results of the treatment of mixed arterial and venous ulcers of the lower limbs with prostaglandin E1 (PGE1) infusion. This study was carried out in 48 consecutive patients. Patients who showed intolerability to PGE1, and patients with peripheral neuropathy, blood or systemic diseases, malignancy and acute wound infections or necrotic tissue on the wound bed were excluded. The patients were separated at random into two main groups: group I (25 patients) received standard treatment and PGE1 infusion. Group II (23 patients) received only standard treatment. Pre‐treatment data indicated the area of ulceration. The number of healed ulcers and the variation in the area of ulceration were considered as endpoints. The endpoints were noticed after 120 days from the beginning of treatment. Healing occurred in 80% of limbs of group I and in 52·2% of limbs of group II patients. The average reduction in area was 92% versus 60% in patients of group I and II, respectively. During the whole treatment period, the incidence of adverse events was 8% in group I: there was one case of headache and one case of headache and hypotension combined. No side effects were recorded in patients of group II. In conclusion, PGE1 infusion is a determinant in the reduction of the healing time of mixed ulcers of the lower limbs.